Regulation and role of catalases during development and oxidative stress in Dictyostelium discoideum - Garcia, Maria Xenia U. (Bell & Howell Information and Learning Company, 2001)
Reactive oxygen species (ROS) are a major source of cellular and DNA damage. ROS also play physiological roles by modulating signaling pathways and transcription factors that control cell proliferation, differentiation and apoptosis. Antioxidant enzymes modulate the levels of ROS in the cell. Thus, studying the regulation of antioxidant enzymes is essential to fully understanding the roles of ROS during stress and differentiation. In this work, I analyzed the regulation and function of the catalase antioxidant enzymes during development and oxidative stress in Dictyostelium discoideum . This work has identified two catalase genes, and shown that each is differentially regulated both temporally and spatially during multicellular development. The cat A gene is expressed throughout growth and development while the cat B gene is only expressed during the final stages of morphogenesis. In late development, the CatB enzyme is exclusively localized to the prespore cells, and the CatA enzyme is found primarily in the prestalk cells. The cell type specific expression was found to be mediated by both transcriptional and posttranscriptional mechanisms. Functional analyses of cat A and cat B mutants showed that the two catalases had distinct functions during the Dictyostelium life cycle. CatA is essential for growing cells to survive oxidative stress. The prespore/spore specific catalase CatB functions to control differentiation and morphogenesis as well as to protect mature spores from oxidative stress. The cat A and cat B genes are not upregulated by H 2 O 2 or UV-light. The induction of DNA repair genes and UV sensitivity were not affected in the cat A mutant, suggesting that catalase does not play a crucial role in the natural resistance of Dictyostelium to UV. Genetic and biochemical studies demonstrated that the loss of CatA activity confers resistance to methanol and acriflavine in Dictyostelium . These observations indicate the catalase activity is not only important in the detoxification of H 2 O 2 but in the metabolism of other xenobiotics as well. Taken together, our studies have demonstrated dual protective and regulatory roles for catalases in controlling ROS levels during Dictyostelium growth and development. They have also established Dictyostelium as a system for studying redox regulation of developmental processes.--Abstract.